The woman they wanted : shattering the illusion of the good Christian wife - Harris, Shannon (Vocalist) (Broadleaf Books, 2023)
As the soon-to-be wife of youth pastor Joshua Harris, Shannon Harris found that nothing in her secular upbringing had prepared her to enter the world of conservative Christianity. When Joshua wrote I Kissed Dating Goodbye, it became a bestseller and helped inspire a national purity movement. Now Shannon's identity became "pastor's wife." Asked to live within a narrow definition of womanhood for almost two decades, she found her worldview was narrowed, her motivations questioned, her behavior examined, until she had been whittled down to an idealized version of femininity envisioned as an extension of her husband and the church. This decidedly patriarchal world, perpetuated even by the other women, began to feel like a slow death. When Sovereign Grace Ministries fell apart due to leadership conflicts, Shannon began to shake off the fog of depression and confusion, and she found her truest self. --